Measurements of jet substructure and jet fragmentation using the ATLAS detector - Javier Llorente Merino (SciPost Physics Proceedings, 2022)
Measurements of the internal properties of jets at the LHC interaction scale allow QCD to be studied in a new energy regime. In this talk, we discuss recent measurements of jet substructure and jet fragmentation, which were performed using data collected by the ATLAS experiment at a centre-of-mass energy of $\sqrt{s}=13$ TeV. The fragmentation properties of jets, such as the jet charge and summed fragmentation function, are measured using charged particles. A comprehensive suite of jet substructure observables is also measured for jets reconstructed with the soft-drop algorithm applied. In addition, a measurement of the Lund plane is performed using charged particles. All of the measurements are corrected for detector effects and are compared to the predictions of state-of-the-art Monte Carlo event generators.